Systemic low-grade C-reactive protein is associated with proximal symptom spread in carpal tunnel syndrome - Karolina Zvonickova; Amber Rhee; Oliver Sandy-Hindmarch; Dominic Furniss; Akira Wiberg; Annina B. Schmid (PAIN Reports, 2024)
Abstract. Introduction:. Neuropathic pain is a highly prevalent condition associated with persistent disability. Some patients with neuropathic pain experience symptom spread outside neuroanatomical boundaries; these patients report more severe sensory symptoms and greater disability. However, the mechanisms behind such symptom spread are not fully understood. Objective:. We used pre-surgical carpal tunnel syndrome (CTS) as a human model system of neuropathic pain to identify differences in the concentration of serologic inflammatory mediators between patients with CTS with territorial symptoms and those with proximal symptom spread to either the elbow or shoulder/neck. Methods:. We performed a post-hoc analysis, comparing levels of serologic inflammatory mediators in a discovery cohort among 3 symptoms spread profiles (n = 55; n = 25 no spread, n = 21 spread to elbow, n = 9 spread to shoulder/neck). We then de-novo analysed the significantly dysregulated mediators in an independent validation cohort (n = 72; n = 34 no spread, n = 16 spread to elbow, n = 22 spread to shoulder/neck). Results:. The discovery cohort revealed higher serum concentrations of C-reactive protein (CRP) and interleukin-6 in patients with any symptom spread proximal to the wrist; interferon-γ was higher in patients with symptom spread to the elbow compared with those without proximal spread. The validation study replicated the association of higher CRP concentrations in patients with proximal spread to the elbow (no spread: median [interquartile range] 2.5 [5.4]; spread to elbow 6.2 [4.6]; spread to shoulder/neck 2.6 [3.7], P = 0.006). No other markers replicated in the validation cohort. Conclusions:. Our findings suggest that proximal symptom spread in the context of neuropathic symptoms is associated with low-grade inflammation.